Quality of life after adult living donor liver transplantation: A longitudinal prospective follow‐up study. Issue 10 (1st February 2013) - Togashi, Junichi; Sugawara, Yasuhiko; Akamatsu, Nobuhisa; Tamura, Sumihito; Yamashiki, Noriyo; Kaneko, Junichi; Sakamoto, Yoshihiro; Aoki, Taku; Hasegawa, Kiyoshi; Kokudo, Norihiro
<x xml:space="preserve">Abstract</x> Aim Patient survival after living donor liver transplantation (LDLT) has improved, but improvement of the health‐related quality of life (HRQOL) of LDLT recipients is also an important issue. The aim of this study was to assess the HRQOL of LDLT recipients from the preoperative period to 18 months following transplantation by prospectively evaluating Short Form‐36 Version 2 (SF‐36v2) scores. Methods Complete longitudinal SF‐36v2 scores were collected from 35 consecutive LDLT recipients prior to surgery and at 3, 6, 12 and 18 months after transplantation. Results HRQOL scores were severely impaired in all dimensions preoperatively. Although the scores improved significantly up to 18 months after transplantation, they remained lower than those of healthy controls in the majority of domains. Impaired scores preoperatively were significantly associated with severity of liver disease represented by a higher Model for End‐Stage Liver Disease (MELD) score and Child–Turcotte–Pugh class C, and scores in such patients improved significantly after LDLT in every dimension at 12 months, indicating that the greater the impairment at the pretransplant stage, the greater the improvement in both physical and mental conditions. Preoperative lower HRQOL scores and higher MELD scores were independently associated with significant physical and mental score gains during the first year after LDLT. Conclusion The findings of the present study may facilitate the development of measures aimed at improving recipient's post‐transplant life and establishing realistic expectations for LDLT recipients.